Higher Education: A Commitment to the Future of our Nations? - Gomez Sanchez Soto, Ruben (2023)
It is reasonable that different nations aspire to a future and that it be built in favor of their citizens. This idea generated interest to start this work. The research began with an analysis of the problems of education in Peru; The figures that were found are calamitous. In addition to this result, it was verified how enrollment in public universities has been decreasing dramatically and steadily, from the year 2000 to 2020. These two facts consolidated the concern about the proposal: higher education: A bet on the future of our nations? Throughout the research, several related topics were discussed and gradually it was visualized that – by having a strong, consolidated, and advanced higher education – one can have more confidence in achieving the future of nations. This expression is based on the level of higher education, in terms of R&D&I, which strengthens the challenges in terms of innovation; thereby achieving a substantial improvement in the technological and pedagogical capacity of the people benefited by this educational level. According to the results of the research, the following expression can be reached: one cannot think about the future of higher education without thinking about the future of our countries. If we want a fairer country, with equity, with more possibilities, we have to guarantee quality and inclusive higher education.